2013
DOI: 10.5194/acp-13-7039-2013
|View full text |Cite
|
Sign up to set email alerts
|

Global mapping of maximum emission heights and resulting vertical profiles of wildfire emissions

Abstract: The problem of characteristic vertical profile of smoke released from wildland fires is considered. A methodology for bottom-up evaluation of this profile is suggested and a corresponding global dataset is calculated. The profile estimation is based on: (i) a semi-empirical formula for plume-top height recently suggested by the authors, (ii) satellite observations of active wildland fires, and (iii) meteorological conditions evaluated for each fire using output of the numerical weather prediction model. Inject… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
108
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(121 citation statements)
references
References 41 publications
11
108
2
Order By: Relevance
“…This leads to lower nocturnal InjH which are amplified by the combination of nighttime stable atmosphere and lower PBL (Sofiev et al, 2013). However some meteorological conditions can intensify fire activity over night, as for example the Santa Ana foehn wind (Sharples, 2009), and keep them running.…”
Section: Physics Of Landscape Fire Plumesmentioning
confidence: 99%
“…This leads to lower nocturnal InjH which are amplified by the combination of nighttime stable atmosphere and lower PBL (Sofiev et al, 2013). However some meteorological conditions can intensify fire activity over night, as for example the Santa Ana foehn wind (Sharples, 2009), and keep them running.…”
Section: Physics Of Landscape Fire Plumesmentioning
confidence: 99%
“…In addition, observations show that under favorable atmospheric conditions strong fires can enhance deep convection, injecting plumes more than 5 km into the free troposphere (Cammas et al, 2009;Fromm et al, 2010;Val Martin et al, 2010;Sofiev et al, 2013). Model studies have also found that limiting fire emissions to the boundary layer underestimates their influence in downwind regions (Cook et al, 2007;Freitas et al, 2007;Brioude et al, 2009;Chen et al, 2009;Jian and Fu, 2014).…”
Section: Biomass Burning Emissionsmentioning
confidence: 99%
“…Several studies have proposed plume models or parameterisation of the top height of the plumes, based on empirical methods or on the use of satellite observations (Tosca et al, 2011;Val Martin et al, 2010). A determination of the vertical profiles of fires emissions at the global scale was proposed by Sofiev et al (2013), based on satellite observations and semi-empirical formulas. An example is shown in Fig.…”
Section: Atmosmentioning
confidence: 99%
“…19, which highlights the importance of meteorology in the day-night variation of the height of fire plumes. It is worth noting that the diurnal variation of the injection height is significant such that one can practically consider two independent data sets, one for daytime and one for night-time, with transition during morning and evening (Sofiev et al, 2013). The influence on ozone can be a combination of injection height and frequency .…”
Section: Atmosmentioning
confidence: 99%